PEMBENTUKAN TARUK (SHOOT) DAN PEMBUNGAAN KENCUR (Kaempferia galanga L.) - Dr. Marina Silalahi, M.Si; Yovita Harmiatun (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Research the formation of shoots and inflorescence the Kaempferia galanga carried out. Rhizoma of the K. galanga used to seedling has 2-3 buds for 30 pots with compost media. The data taken is qualitative such as the process of formation shoot and inflorescence. The results that the rhizoma colour affected the shoots, which were light rhizomes forming the green shoots while dark rhizomas formed red shoots. The early formation shoots form a solid cone surrounded by leaf scales. The leaves are shaped like a collar that surrounds the pseudostem and then turns into a tube, then like a funnel. The early the leaves grow in a vertical direction and then slowly in a horizontal direction. Mature leaves are the direction is almost parallel to the ground surface. After forming 2-3 mature leaves, will be forms the inflorescence candidate that risen from the tip of the pseudostem. A week after inflorescence appears, the flower will bloom. The flower blooms perfectly at 06.00-07.00 and after that it will wither. After the flower is 12-24 hours the flower will fall out. Each inflorescence has between 5-9 flowers and blooms every 2-3 days. Although K. galanga produces flowers, no fruit was formed in this study. Keywords: Kaempferia galanga, shoot, inflorescence